PRAKTIK NGAMPANG DAN PANDANGAN TOKOH MUI TERHADAP PERMASALAHAN NGAMPANG DI KECAMATAN SINTANG, KABUPATEN SINTANG - Alfarisi, Muhammad Adib; Ma'u, Dahlia Haliyah; Muzammil, Sadulloh (Al-Usroh, 2023)
This article discusses the practice of Ngampang and the views of MUI leaders on the Ngampang problem in Sintang District, Sintang Regency. The purpose of this research is to find out: 1) Problems of Ngampang Practice in Sintang Regency; 2) The views of MUI Sintang figures on the problem of Ngampang practice in Sintang District, Sintang Regency. This study uses a descriptive qualitative method. The data sources in this study consisted of primary and secondary sources, namely: 1) Primary sources were MUI (Indonesian Ulema Council) figures at the MUI Office in Sintang District, Sintang Regency; 2) Secondary sources in the form of literature that provide information related to pregnant out of wedlock in the form of scientific papers, theses, journals, theses, dissertations, Marriage Law, KHI (Islamic Law Compilation), MUI Fatwa, and techniques used are in-depth interviews and documentation. Meanwhile, in analyzing the data, the researcher used an interactive model of data analysis method and verified the validity of the data by conducting a member check. Based on data analysis, the researcher concluded that the practice of ngampang or pregnant out of wedlock is a problem and a case in Sintang District. In pregnant out of wedlock marriages, they first customary traditional marriages, then legally marry according to state law and are registered with the marriage registration institution. There are three views of MUI leaders on the problem of ngampang practice, namely: first, it is permissible to marry for various reasons, namely social considerations, justice, and benefit. Second, it is permissible on condition that the man who marries her is the man who impregnated her. Third, it is not allowed, because in order to maintain the purity of religious teachings, marriage is forbidden and is an act of adultery (forbidden) which MUI is based on MUI FATWA No. 11 of 2012.